Development of plasmonic-based sensor for highly sensitive and selective detection of dopamine - Kamal Eddin, Faten Bashar; Yap, Wing Fen; Liew, Josephine Ying Chyi; Muhamad Fauzi, Nurul Illya; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Abdullah, Huda (Elsevier, 2023)
The rapid and specific detection of dopamine (DA) is of great importance for diagnosis of neurodegenerative diseases. Surface plasmon resonance (SPR) sensors are promising tools for real time monitoring of biomolecular interactions. However, the sensitivity of such sensors necessitates improvement. For this purpose, graphene oxide (GO) was employed in this work to prepare the sensor chip. Interestingly, the proposed sensor possessed an excellent performance with high sensitivity of 0.2148—¦ /pM and affinity constant of 2.148 TMˆ’ 1 . The precision for nine replicate detections of 100 fM was 0.125 (RSD). Significantly, this plasmonic based sensor has potential to determine DA in real time within 5 min. Moreover, it showed excellent reproducibility, repeatability, and selectivity to common interfering species, as well as outstanding storage stability. Considering its simple fabrication, high sensitivity and other sensing characteristics, it was found that this optical sensor showed considerable promise as a reliable technique for rapid detection and in-field measurement.